Evaluation of How Financial Performance Affects Profitability - Anggi Puspita Sari (Denisya Smart Consulting, 2023)
The goal of this research project is to find out if the profitability of PT Bank Muamalat Tbk is influenced by financial ratios. The research sample, chosen by the application of purposive sampling, consists of the financial statements of PT Bank Muamalat Tbk from 1998 to 2021. In this study, data is processed using the Least Squares (LS) Method, and multiple linear regression tests are utilized to examine conventional assumptions. Eviews 12 is the data processing software utilized in this instance. The study's findings demonstrate that there is no appreciable relationship between Bank Muamalat Indonesia's ROA profitability and the financial parameters FRD, BOPO, NIM, or CAR. The profitability of Bank Muamalat Indonesia is significantly impacted by the non-performing financing (NPF Nett) financial ratio.